2021
DOI: 10.1007/s10096-021-04185-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of clinical carbapenem-resistant Enterobacterales from Qatar

Abstract: One hundred forty-nine carbapenem-resistant Enterobacterales from clinical samples obtained between April 2014 and November 2017 were subjected to whole genome sequencing and multi-locus sequence typing. Klebsiella pneumoniae (81, 54.4%) and Escherichia coli (38, 25.5%) were the most common species. Genes encoding metallo-β-lactamases were detected in 68 (45.8%) isolates, and OXA-48-like enzymes in 60 (40.3%). blaNDM-1 (45; 30.2%) and blaOXA-48 (29; 19.5%) were the most frequent. KPC-encoding genes were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“… The reporting proportion of non-CP-CRE and carbapenemase among CREc/CNSEc (Rimrang et al, 2012 ; Del Franco et al, 2015 ; Lefebvre et al, 2015 ; Baran and Aksu, 2016 ; Dupont et al, 2016 ; Jeong et al, 2016 ; Sharma et al, 2016 ; Grundmann et al, 2017 ; Karlowsky et al, 2017 ; Marimuthu et al, 2017 ; Trepanier et al, 2017 ; Abd El Ghany et al, 2018 ; Dagher et al, 2018 ; Senchyna et al, 2019 ; Al-Farsi et al, 2020 ; Abid et al, 2021 ; Huang et al, 2021a ; Musila et al, 2021 ; Tickler et al, 2021 ; Yan et al, 2021 ). …”
Section: Discussionmentioning
confidence: 99%
“… The reporting proportion of non-CP-CRE and carbapenemase among CREc/CNSEc (Rimrang et al, 2012 ; Del Franco et al, 2015 ; Lefebvre et al, 2015 ; Baran and Aksu, 2016 ; Dupont et al, 2016 ; Jeong et al, 2016 ; Sharma et al, 2016 ; Grundmann et al, 2017 ; Karlowsky et al, 2017 ; Marimuthu et al, 2017 ; Trepanier et al, 2017 ; Abd El Ghany et al, 2018 ; Dagher et al, 2018 ; Senchyna et al, 2019 ; Al-Farsi et al, 2020 ; Abid et al, 2021 ; Huang et al, 2021a ; Musila et al, 2021 ; Tickler et al, 2021 ; Yan et al, 2021 ). …”
Section: Discussionmentioning
confidence: 99%
“…The most common carbapenemase genes observed in this study are those that encode OXA-48-like carbapenemase lactamases. A previous report on CRE infections in Qatar in the general population (median age 57) and using various sample sources reported NDM-1 and NDM-7 as the most common carbapenemases [ 18 ]. However, investigating a sub-population, pediatric UTIs in the study case show a shift in the distribution of carbapenemases.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data describing carbapenem-resistant Enterobacteriaceae (CRE) from the Arabian Gulf region among the pediatric population. In Qatar, only one study conducted on different clinical samples from different age groups, presented at the infectious disease forum in 2019, reported that NDM and OXA-48 are the predominant carbapenemases in Qatar and are associated with high overall mortality [ 18 ]. The epidemiology of CREs in the adult population is well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…However, the theoretical benefit of rapid organism identification together with rapid detection of antimicrobial resistance markers to decrease length of hospital stay and improve mortality in BSI caused by Enterobacterales is yet to be determined ( 3 ). The actual clinical impact of our rapid diagnostic approach lies on improving antimicrobial stewardship (ASP) by shortening the time to optimal antimicrobial therapy in settings with high prevalence of antimicrobial resistance among enteric Gram-negative bacteria ( 8 ).…”
Section: Discussionmentioning
confidence: 99%